Hubungan Tingkat Stres Dengan Kejadian Timbulnya Acne Vulgaris Pada Siswi Kelas XII DI MAN 2 Kota Bogor Tahun 2023 - Eri Nurlaeli; Nining Rukiyah; Eka Rokhmiati Wahyu Purnamasari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Stress is a condition in which all non-specific demands require an individual to respond or perform an action. Stress is one of the causes of acne vulgaris, stress occurs due to a stimulus that produces a reaction in the brain. Stress levels are divided into three parts: mild stress, moderate stress and severe stress. Acne vulgaris is a condition in which skin is caused by blockage or inflammation by the hair volicle and also the sebaseal gland, also known as a unit of pilobasea. in the form of non-inflammatory comedies, papule inflammation, and can be mixed with lesions. The type of method used is quantitative research with cross sectional design. It was found that respondents with mild stress levels had mild acne 2 out of 2 respondents (100%), while those with moderate stress had more moderate acne, 49 out of 55 respondents with presentation (89%) and 6 out of 11 respondents with presentation (54.55%). And show the results of the Rank Sprearman P Vallue 0.004 < 0.05.